PENGARUH APLIKASI KECERDASAN BUATAN TERHADAP PRESTASI MAHASISWA UIN SUNAN AMPEL SURABAYA (TINJAUAN DELON MCLEAN IS MODEL) - Rahma, Novia; Amrozi, Yusuf; Milad, Mohammad Khusnu (PSRE UNIMUS, 2025)
This study assesses the impact of artificial intelligence (AI) applications on academic performance among students of the Faculty of Science and Technology at Sunan Ampel State Islamic University Surabaya using the DeLone & McLean IS Success Model. A descriptive quantitative method was employed, collecting data from 100 students via online questionnaires. Regression analysis results indicate that system quality, information quality, and service quality contribute to academic performance by 20.2%, 10.8%, and 16.7% respectively, with a total contribution of 28.3%. The findings suggest that while AI applications play a role in academic performance, their impact is still limited. Future research is recommended to involve a broader respondent base and explore alternative theoretical models to gain a more comprehensive understanding of AI’s impact on education. This study aims to provide valuable insights for educational institutions in integrating AI technology to enhance learning quality.